Thickening method of low-viscosity photoresist
By using the double-layer spin coating and baking method of low viscosity photoresist in semiconductor packaging and testing, the problem that existing photoresist equipment is difficult to spray high-thickness resist layer, and a higher-thickness resist layer is achieved , reduces production costs and improves product quality.
Patent Information
- Application Number
- CN202411618354.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-13
AI Technical Summary
In the semiconductor packaging and testing manufacturing industry, it is difficult for existing photoresist equipment to spray high viscosity photoresist, resulting in insufficient thickness of the resist layer and unable to meet the requirements of high current support and high bump height.
The low-viscosity photoresist is used to break through the thickness limitation of single-layer photoresist by two spin coatings and baking methods to achieve thickening of the resist layer. The specific steps include spin-coating the first layer of photoresist on the grown Ti-Cu film seed layer, performing the first soft baking and cooling, and then spin-coating the second layer of photoresist, performing the second soft baking and cooling. .
It has achieved a thicker resist layer based on the existing low-viscosity photoresist, which reduces the equipment requirements of high-viscosity photoresist, reduces the time for equipment investment and material testing, and improves the corrosion resistance layer. Uniformity and stability.
Smart Images

Figure CN119472174A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for thickening a low-viscosity photoresist and belongs to the field of photolithography technology. Background Art
[0002] In the semiconductor packaging and testing manufacturing industry, Bumping technology is a process that connects the exposed metal leads of integrated circuits to the metal bumps on the ceramic substrate, which can improve the reliability and performance of the circuit. With the help of Bumping technology, the intermediate links can be reduced, which is conducive to reducing production costs.
[0003] However, bumping technology also faces some challenges. The height of the metal bump is determined according to the package design requirements. Usually, in order to increase the reliability of the package and support higher currents, the copper bump may need to be higher. As a result, there are very high requirements for the thickness of the required anti-corrosion layer. Not only does it require higher resolution, less solvents, and high-viscosity and high-hardness resins to support the glue thickness required for the bumps, but also the conventional glue coating equipment in the industry is difficult to have the ability to spray such high-viscosity photoresist. Even if it does, the cost of the equipment hardware is also quite high. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, the present invention provides a method for thickening a low-viscosity photoresist, which can break through the thickness limit of the photoresist and can make a thicker anti-corrosion layer with a lower viscosity photoresist.
[0005] The technical solution adopted by the present invention to solve its technical problem is: A method for thickening a low-viscosity photoresist comprises the following steps: Spin coating a first layer of photoresist on the wafer on which the Ti-Cu thin film seed layer has been grown; Performing a first soft bake on the wafer; the temperature of the first soft bake is lower than the temperature specified in the technical instruction manual of the photoresist, and the time of the first soft bake is shorter than the time specified in the technical instruction manual of the photoresist; performing a first cooling on the wafer; Spin coating a second layer of photoresist on the wafer; performing a second soft bake on the wafer; The wafer is cooled for a second time to obtain an anti-corrosion layer.
[0006] The low-viscosity photoresist thickening method provided by the present application can effectively break through the limitation of the thickness of the single-layer photoresist and realize the thickening of the anti-corrosion layer through two spin coatings and baking. This technology allows a thicker anti-corrosion layer to be made on the basis of the existing low-viscosity photoresist, which not only reduces the requirements of the high-viscosity photoresist on the equipment, but also greatly reduces the equipment investment and the time of material testing. In addition, the temperature and time control of the first soft baking make the first layer of photoresist have good film quality and bonding force while the solvent is volatilized, laying a foundation for the subsequent high-quality spin coating of the second layer of photoresist.
[0007] As a preferred embodiment, before the first soft baking step, there is a step of performing a first EBR treatment on the first layer of photoresist.
[0008] Adding the EBR (Edge Bead Removal) treatment step helps improve the clarity of the pattern in the photolithography process and prevents the excess photoresist generated at the edge during the spin coating process from affecting the accuracy of subsequent processes. The first EBR treatment is performed after the photoresist is spin-coated, ensuring that the excess photoresist at the edge is cleaned before the initial soft bake to avoid interference with the subsequent high-quality spin coating of the second layer of photoresist, which is beneficial to improving the overall uniformity and processing quality of the resist layer.
[0009] As a preferred embodiment, the first EBR treatment adopts chemical edge washing.
[0010] Using chemical edge washing for EBR treatment can accurately control the edge washing effect and reduce the impact of residual glue on subsequent processes. The chemical method has the ability to efficiently remove edge photoresist, which can reduce the physical damage that may be caused by mechanical edge washing, ensure that the edge photoresist film of the wafer remains clean, and further improve the edge stability of the photoresist coating.
[0011] As a preferred embodiment, the rotation speed of the first EBR treatment is lower than the rotation speed used when spin coating the first layer of photoresist.
[0012] By reducing the speed during EBR processing, the removal range of photoresist at the edge of the wafer can be better controlled to avoid excessive EBR processing due to excessively high speed, thereby weakening the effective thickness of the photoresist. Fine adjustment of the speed helps to improve the uniformity of the photoresist, especially in processes with high thickness requirements, ensuring the integrity of the thick film.
[0013] As a preferred embodiment, the coating capacity of the coating machine used for spin coating photoresist is adapted to solutions with viscosities of 10 cP to 800 cP. This ensures that the coating equipment can flexibly handle photoresists of different viscosity ranges, and this requirement is relatively low, which can be achieved by most coating machines, effectively reducing the need for equipment hardware upgrades and avoiding material replacement problems caused by equipment.
[0014] As a preferred embodiment, the temperature of the hot plate used for soft baking can be adjusted within a range of 50° C. to 150° C. The wide temperature adjustment range allows for flexible selection of optimal soft baking parameters according to different photoresists and process requirements.
[0015] As a preferred embodiment, the viscosity of the photoresist used is greater than or equal to 400 cP and less than 800 cP. The photoresist of corresponding viscosity can enhance the mechanical strength and precision tolerance of the photoresist when forming a thicker coating in one spin coating, and meet the requirements of the copper pillar bump process for thick film. In addition, through subsequent spin coating and soft baking, the uniformity and stability of the resist layer can be maintained while ensuring the thickness of the resist layer.
[0016] As a preferred embodiment, the temperature of the first soft baking is 100°C to 120°C, and the time is 5min to 10min. By appropriately reducing the soft baking temperature and time, the evaporation rate of the solvent in the photoresist can be effectively controlled to avoid defects such as cracks or pinholes in the film layer caused by rapid evaporation. Based on a photoresist with a viscosity greater than or equal to 400cP, the optimized temperature and time settings not only improve the surface quality of the photoresist film, but also ensure the bonding force between the photoresist films in the subsequent spin coating process, thereby improving the overall thickness and performance of the final anti-etching layer.
[0017] As a preferred embodiment, the temperature of the first cooling is room temperature, and the time is 30s. 30 seconds of room temperature cooling can take away the heat of the photoresist surface layer, which is conducive to the next spin coating. The short cooling time can stabilize the photoresist layer, and the room temperature cooling avoids cooling too fast, and will not significantly increase the process time, thereby improving production efficiency.
[0018] As a preferred embodiment, before the second soft baking step, there is a step of performing a second EBR treatment on the second photoresist layer. By performing the EBR treatment after the second spin coating, the edges of each layer of photoresist can be further ensured to be neat, which helps to ensure the uniformity of the stacked photoresist.
[0019] As a preferred embodiment, the second EBR treatment adopts chemical edge washing.
[0020] As a preferred embodiment, the rotation speed of the second EBR treatment is lower than the rotation speed used when spin coating the second layer of photoresist.
[0021] As a preferred embodiment, the temperature of the second cooling is room temperature and the time is 30 seconds.
[0022] The beneficial effects of the present invention are as follows: the method for thickening the low-viscosity photoresist of the present invention is simple and easy to implement, can break through the limit of the photoresist layer thickness, expand the applicable process window of the photoresist thickness, and use the low-viscosity photoresist to make a high-thickness anti-corrosion layer, which is beneficial to reducing production costs, avoiding the trouble of changing the type of photoresist and changing the glue coating machine due to different requirements for the height of the bumps, and is beneficial to the stability of product quality.
[0023] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or understood by practicing the present application. The purpose and other advantages of the present application can be realized and obtained by the structures particularly pointed out in the written description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of the process of growing metal bumps on a wafer in the prior art.
[0025] Figure 2 This is a schematic diagram of the occurrence of blistering when the height of the metal bump is required to be greater than the maximum thickness of the photoresist.
[0026] Figure 3 It is a schematic diagram of the process of growing metal bumps on a wafer after applying the present application.
[0027] Figure numerals: 1, wafer; 21, titanium layer; 22, copper layer; 3, anti-etching layer; 31, first photoresist layer; 32, second photoresist layer; 4, metal bump. DETAILED DESCRIPTION
[0028] The embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0029] The disclosure below provides many different embodiments or examples to implement different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplification and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed.
[0030] Unless otherwise specified, all technical and scientific terms used herein have the standard meaning in the field to which the claimed subject matter belongs. If there are multiple definitions for a term, the definition herein shall prevail.
[0031] Conventional processes for making metal bumps in the semiconductor industry include: Figure 1 As shown, photoresist is spin-coated on wafer 1 and cured to form an anti-etching layer 3, and then metal bumps 4 are grown where there is no anti-etching layer 3. Usually, the thickness of the anti-etching layer 3 is 20μm, and the metal bumps 4 are copper bumps with a height of 15μm. Nowadays, the height of copper pillar bumps is generally required to be higher and higher, such as 25μm, while the thickest anti-etching layer formed by photoresist with low viscosity can only reach 20μm. At this time, if a higher metal bump is to be grown, it is easy to cause plating, such as Figure 2 As shown. Plating errors can cause cold solder joints and missing solder joints in substrate packaging. If a photoresist with higher viscosity is used, expensive equipment will need to be used. Due to the change in the type of photoresist and the coating machine, other equipment and process parameters must be adjusted and tested multiple times accordingly.
[0032] In view of the above problems, the present invention provides a method for thickening a low-viscosity photoresist, comprising the following steps: S1: Spin coating a first layer of photoresist on the wafer on which the Ti-Cu thin film seed layer has been grown.
[0033] S2: Perform the first soft bake on the wafer.
[0034] S3: Cooling the wafer for the first time.
[0035] S4: Spin-coat a second layer of photoresist on the wafer.
[0036] S5: performing a second soft bake on the wafer.
[0037] S6: Cooling the wafer for a second time to obtain an anti-etching layer.
[0038] The temperature of the first soft baking in step S2 is lower than the temperature specified in the technical instruction manual of the photoresist, and the time of the first soft baking is shorter than the time specified in the technical instruction manual of the photoresist. The Ti-Cu thin film seed layer refers to a thin titanium layer 21 deposited on the wafer before the wafer is processed in step S1, and then a thin copper layer 22 is deposited.
[0039] The embodiment of the present application can effectively break through the limitation of the thickness of a single layer of photoresist by two times of spin coating and baking, and realize the thickening of the anti-corrosion layer. This technology allows a thicker anti-corrosion layer to be made on the basis of the existing low-viscosity photoresist, which not only reduces the equipment requirements of high-viscosity photoresist, but also greatly reduces the equipment investment and material testing time. In addition, the temperature and time control of the first soft baking make the first layer of photoresist have good film quality and bonding force while evaporating the solvent, laying a foundation for the subsequent high-quality spin coating of the second layer of photoresist.
[0040] Using this method to form a resist layer and then grow a metal bump with a larger height, Figure 3As shown, for example, the thickness of the first photoresist layer 31 is 20 μm, and the thickness of the second photoresist layer 32 is 10 μm. After curing, a total of 30 μm of anti-corrosion layer 3 is formed. At this time, a 25 μm high copper bump is grown, which will not be higher than the anti-corrosion layer 3, and no bridging will occur. Therefore, the present invention can be used to make high-quality metal bumps with a large height based on existing materials and processes. Compared with methods such as changing the photoresist type, it has the smallest change, the smallest cost and the lowest risk, and meets the product process requirements at the same time.
[0041] When implementing the present invention, the appropriate coating speed and soft baking temperature and time can be selected according to the specific photoresist material and photolithography process. The specific implementation method is a double-layer coating method: coating-soft baking-EBR edge washing-cooling-coating-soft baking-EBR edge washing-cooling. The conventional coating process is a single-step coating. This method uses the method of coating the photoresist twice to stack the thickness of the film. Since the composition, properties, and molecular structure of the photoresist coated twice are consistent, even if two overlapping coatings are performed, the bonding force between the two layers of glue will not be greatly affected. The detailed description is as follows: Before step S2, there is step S11: performing a first EBR treatment on the first layer of photoresist.
[0042] That is, the method steps become: S1: Spin coating a first layer of photoresist on the wafer on which the Ti-Cu thin film seed layer has been grown.
[0043] S11: performing the first EBR treatment on the first layer of photoresist.
[0044] S2: Perform the first soft bake on the wafer.
[0045] S3: Cooling the wafer for the first time.
[0046] S4: Spin-coat a second layer of photoresist on the wafer.
[0047] S5: performing a second soft bake on the wafer.
[0048] S6: Cooling the wafer for a second time to obtain an anti-etching layer.
[0049] The first EBR treatment adopts a physical method or a chemical method, preferably a chemical method for edge washing, and the rotation speed of the first EBR treatment is lower than the rotation speed used when the first layer of photoresist is spin-coated.
[0050] The first EBR treatment can remove excess photoresist at the edge of the wafer to avoid distortion or irregularity of the edge of the first layer of photoresist. EBR treatment before the first soft bake helps to improve the edge uniformity of the first layer of photoresist, ensure the quality of the subsequent second layer of photoresist spin coating and exposure process, and is conducive to spin coating the second layer of photoresist on a flat surface and to the flatness of the top surface of the second layer of photoresist itself.
[0051] Preferably, the temperature of the first cooling is room temperature and the time is 30 seconds. 30 seconds of room temperature cooling can take away the heat of the photoresist surface layer, which is beneficial for the next spin coating. The short cooling time can stabilize the photoresist layer, and room temperature cooling avoids cooling too fast, and will not significantly increase the process time, thereby improving production efficiency. In addition, the temperature of the second cooling can also be room temperature and the time is 30 seconds. In a preferred embodiment, before step S5, there is a step S41: performing a second EBR treatment on the second layer of photoresist.
[0052] That is, the method steps become: S1: Spin coating a first layer of photoresist on the wafer on which the Ti-Cu thin film seed layer has been grown.
[0053] S2: Perform the first soft bake on the wafer.
[0054] S3: Cooling the wafer for the first time.
[0055] S4: Spin-coat a second layer of photoresist on the wafer.
[0056] S41: performing a second EBR treatment on the second layer of photoresist.
[0057] S5: performing a second soft bake on the wafer.
[0058] S6: Cooling the wafer for a second time to obtain an anti-etching layer.
[0059] Or: S1: Spin coating a first layer of photoresist on the wafer on which the Ti-Cu thin film seed layer has been grown.
[0060] S11: performing the first EBR treatment on the first layer of photoresist.
[0061] S2: Perform the first soft bake on the wafer.
[0062] S3: Cooling the wafer for the first time.
[0063] S4: Spin-coat a second layer of photoresist on the wafer.
[0064] S41: performing a second EBR treatment on the second layer of photoresist.
[0065] S5: performing a second soft bake on the wafer.
[0066] S6: Cooling the wafer for a second time to obtain an anti-etching layer.
[0067] The second EBR treatment is performed by a physical method or a chemical method, preferably a chemical method for edge washing, and the rotation speed of the second EBR treatment is lower than the rotation speed used when the second layer of photoresist is spin-coated.
[0068] The purpose of the second EBR process is to remove excess photoresist at the edge of the wafer (often called edge beads) to avoid particle contamination or other defects in subsequent processes. This ensures that the edge of the wafer remains clean, thereby improving the reliability of subsequent processes.
[0069] The coating capacity of the coating machine used for spin coating the photoresist in step S1 and step S4 is adapted to the solution with a viscosity of 10 cP to 800 cP. This requirement is relatively low and can be achieved by most coating machines, which effectively reduces the need for equipment hardware upgrades.
[0070] The temperature of the hot plate used for soft baking in step S2 and step S5 can be adjusted in the range of 50°C to 150°C. The wide temperature adjustment range allows the soft baking process to flexibly adapt to different types of photoresist materials. By accurately controlling the baking temperature, the solvent can be gradually volatilized at an appropriate temperature to avoid premature hardening or cracking of the photoresist film due to excessively high temperature, thereby ensuring the uniformity and quality of the photoresist layer and reducing process defects.
[0071] In some embodiments, the viscosity of the photoresist used is greater than or equal to 400 cP and less than 800 cP. Accordingly, the temperature of the first soft baking is 100°C to 120°C, and the time is 5 min to 10 min. Moderate soft baking temperature and time control help the gradual volatilization of the solvent in the photoresist, preventing the photoresist surface from hardening too quickly or causing stress cracks at high temperatures. This temperature range can effectively maintain the uniformity of the photoresist layer, and ensure the interlayer bonding force in the subsequent coating process, and finally form a stable thick film structure.
[0072] Application Cases For example, the viscosity of conventional Class A photoresist 500cP can make a maximum 15μm thick anti-corrosion layer, but the current product process requires a 25μm thick anti-corrosion layer, and a single coating of Class A photoresist cannot meet the product process requirements. At this time, using Class B high viscosity 800cP photoresist instead, it is necessary to consider the increase in cost and material testing time, and it is also necessary to bear the risk that the machine in the factory cannot match the high viscosity photoresist coating, and even need to re-purchase a new machine for this purpose, which is easy to cause great losses and waste in cost and time. Using the coating method of the present invention to carry out the glue coating operation, the glue thickness can be accumulated, and the maximum anti-corrosion layer thickness is expected to reach 25μm~40μm after two coatings, which can meet the product process requirements, and use the original photoresist materials and glue coating machines in the factory, which has great improvements in risk control, material cost and time reduction.
[0073] Therefore, the embodiments of the present application can break through the limit of the thickness of the original photoresist. In the semiconductor industry, thick photoresist processes are commonly used for products produced with the participation of bumping technology. The invention can effectively solve the problem that the viscosity of the photoresist itself is insufficient or the hardware capability of the machine cannot prepare a high thickness anti-corrosion layer. The method is simple and easy to implement, has significant effects, and can be widely used in the field of semiconductor manufacturing. By implementing the present invention, the quality and stability of semiconductor products can be effectively improved, production costs can be reduced, and the sustainable development of the semiconductor industry can be promoted.
[0074] In the description of this specification, the description with reference to the terms "one embodiment", "certain embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0075] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A method for thickening a low-viscosity photoresist, characterized in that: The following steps are involved: Spin coating a first layer of photoresist on the wafer on which the Ti-Cu thin film seed layer has been grown; performing a first soft bake on the wafer; The temperature of the first soft baking is lower than the temperature specified in the technical instruction manual of the photoresist, and the time of the first soft baking is shorter than the time specified in the technical instruction manual of the photoresist; performing a first cooling on the wafer; Spin coating a second layer of photoresist on the wafer; performing a second soft bake on the wafer; The wafer is cooled for a second time to obtain an anti-corrosion layer.
2. The method for thickening a low-viscosity photoresist according to claim 1, characterized in that: Before the first soft baking step, there is a step of performing a first EBR treatment on the first layer of photoresist.
3. The method for thickening a low-viscosity photoresist according to claim 2, characterized in that: The first EBR treatment adopts chemical method to wash the edges.
4. The method for thickening a low-viscosity photoresist according to claim 2, characterized in that: The rotation speed of the first EBR treatment is lower than the rotation speed used when spin coating the first layer of photoresist.
5. The method for thickening a low-viscosity photoresist according to claim 1, characterized in that: The spraying capacity of the coating machine used for spin coating photoresist is suitable for solutions with viscosities of 10cP~800cP.
6. The method for thickening a low-viscosity photoresist according to claim 1, characterized in that: The temperature of the hot plate used for soft baking can be adjusted in the range of 50℃~150℃.
7. The method for thickening a low-viscosity photoresist according to claim 1, characterized in that: The viscosity of the photoresist used is greater than or equal to 400 cP and less than 800 cP.
8. The method for thickening a low-viscosity photoresist according to claim 7, characterized in that: The temperature of the first soft baking is 100° C. to 120° C., and the time is 5 min to 10 min.
9. The method for thickening a low-viscosity photoresist according to claim 1, characterized in that: The temperature of the first cooling is room temperature and the time is 30s.
10. The method for thickening a low-viscosity photoresist according to claim 1, characterized in that: Before the second soft baking step, there is a step of performing a second EBR treatment on the second layer of photoresist.
Citation Information
Patent Citations
Patterned photoresist layer forming method and wafer-stage chip packaging method
CN104516194A
Coating formation method
CN104952704A
Manufacturing method of semiconductor device
JP2012069823A
Removable laundry drying device rail release two fold
KR1020230164818A
Point of Use Solvent Mixing for Film Removal
US20220334485A1